Negligencia parental en y su incidencia la conducta de una adolescente de 15 años del Centro de Acogimiento “Mi Rinconcito” - Apolo Álvarez, Dayana Lisseth (2023)
This case study is aimed at analyzing and investigating parental neglect and behavioral problems in adolescents. Omissions and neglect in parental care are part of the predisposing factors and a precipitating event of psychological and behavioral disorders in the 15-year-old adolescent patient. The consequences of parental neglect on the adolescent's behavior are internalized as depression, somatic problems, self-inflicted injuries and suicidal ideation. As well as externalized problems, such as antisocial behavior, drug use, aggressive behavior and disorders such as oppositional defiant disorder. For this reason, it was pertinent to use a quantitative and qualitative evaluation methodology, through clinical observation, interview, clinical history and psychometric reagents. The instruments applied were the Childhood Depression Questionnaire (CDI), the SACKS incomplete sentences test and the SNAP-IV questionnaire. The results obtained allowed determining the presumptive diagnosis of oppositional defiant behavior disorder 313.81, in addition to depressive symptomatology. Therefore, the treatment was carried out from the cognitive-behavioral approach, where techniques and procedures were used, including social skills training, breathing techniques, behavioral activation, cognitive restructuring and problem-solving therapy. With the purpose of working on the defiant attitude, disobedience and aggressive behavior that causes problems in the interaction with others.